O controle da publicidade e a publicidade do controle: proposta de aprimoramento do Estado democrático por meio da contribuição dos Tribunais de Contas para a realização do debate público sobre a gestão pública - Gustavo Terra Elias (2014)
Democracy demands legitimacy from the Government, who must implement, through public administration, the will of the people imprinted in the Constitution and the laws of the land. The legitimacy of political power is not limited to the moment in which the representatives are invested therein through elections. The manner in which public service is implemented, as well as the State policys guidelines, must also be examined in order to ascertain if the State is democratically legitimate. Therefore, public and democratic oversight is imperative in order to publicize State policy, thus allowing the society to determine whether the employed means and the results obtained thereof are legal, legitimate and efficient. According to the deliberative democracy theory, adopted in this work, citizens can also carry out oversight measures, which are undertaken for benefit of the public. Hence, the public must be aware of the performance of the State, who is historically reluctant to act transparently. Furthermore, institutions that are in charge of debating State performance and provide transparency are underwhelming. Such is the case of the Parliament, who has displayed frailty in overseeing the Administration. The media, often co-opted by the administration or by capitalists groups, also fails to provide the society with impartial and truthful information on the administrations performance. In this context, the present research explores the potential of the Courts of Audit to be exploited as oversight institutions, promoting public debate, with public oversight and media proximity. The main goal is to render public administration effectively transparent, allowing society to exercise public autonomy by participating in and overseeing State affairs, creating new arenas and democratic oversight instruments, supplementary yet connected to the institutional oversight undertaken by the Courts of Audit, which can pressure the government to rationally justify its policies before public opinion.